2021
DOI: 10.3389/fonc.2021.658608
|View full text |Cite
|
Sign up to set email alerts
|

LCT-3d Induces Oxidative Stress-Mediated Apoptosis by Upregulating Death Receptor 5 in Gastric Cancer Cells

Abstract: Gastric cancer is a global health problem. In this study, we investigate the role of a novel Indole derivative, named LCT-3d, in inhibiting the growth of gastric cancer cells by MTT assay. The Western blotting results showed that LCT-3d modulated the mitochondrial-related proteins and Cleaved-Caspases 3/9, to induce cell apoptosis. The up-regulation of Death receptor 5 (DR5) in MGC803 cells was observed with LCT-3d treatment. Knockdown of DR5 on MGC803 cells partially reversed the LCT-3d-induced mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Another study showed that silencing SIRT6 induced ferroptosis in gastric cancer cells by inducing inactivation of Keap1-Nrf2 and low expression of GPX4, thereby improving the sensitivity of gastric cancer cells to sorafenib [ 87 ]. It has also been shown that ROS accumulation activates the Keap1-Nrf2 signaling pathway in gastric cancer cells, thereby inhibiting apoptosis in gastric cancer cells [ 88 ]. However, LCT-3d induces oxidative stress and apoptosis in gastric cancer cells by upregulating death receptor 5, a process unaffected by Nrf2 activation [ 88 ].…”
Section: Regulation Of Cell Death In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that silencing SIRT6 induced ferroptosis in gastric cancer cells by inducing inactivation of Keap1-Nrf2 and low expression of GPX4, thereby improving the sensitivity of gastric cancer cells to sorafenib [ 87 ]. It has also been shown that ROS accumulation activates the Keap1-Nrf2 signaling pathway in gastric cancer cells, thereby inhibiting apoptosis in gastric cancer cells [ 88 ]. However, LCT-3d induces oxidative stress and apoptosis in gastric cancer cells by upregulating death receptor 5, a process unaffected by Nrf2 activation [ 88 ].…”
Section: Regulation Of Cell Death In Gastric Cancermentioning
confidence: 99%
“…It has also been shown that ROS accumulation activates the Keap1-Nrf2 signaling pathway in gastric cancer cells, thereby inhibiting apoptosis in gastric cancer cells [ 88 ]. However, LCT-3d induces oxidative stress and apoptosis in gastric cancer cells by upregulating death receptor 5, a process unaffected by Nrf2 activation [ 88 ]. This suggests that the inhibitory effect of the Nrf2 pathway on apoptosis is weak and not readily apparent when other proapoptotic signals are activated.…”
Section: Regulation Of Cell Death In Gastric Cancermentioning
confidence: 99%